Establishing technical and tactical performance goals for elite men´s beach volleyball players - Palao, J. M.; Hernandez-Hernandez, E.; Lopez-Martinez, A. B.; Manzanares, P.; Valades, D.; Ortega-Toro, E. (Journal of Sport and Human Performance, 2018)
The purpose of this paper was to establish the technical and tactical performance goals for elite men´s beach volleyball players. The process for calculation and analysis was carried out in three stages: 1) establishing the criteria to analyze and monitor; 2) data collection (match observation) as well as descriptive (mean, standard deviation, baseline of won and lost sets, and percentiles) and inferential analyses (Chi-Square Test and likelihood ratio) of the data to compare won/lost sets; and 3) establishing performance goals. Eight performance goals for technical-tactical actions to control player´s actions in training and in competition were established. The data obtained are applicable for peak performance men´s beach volleyball (World Tour) or for a similar level of competition.